Pemanfaatan Teknologi AI dalam Pembuatan Media Pembelajaran Organ Tubuh Manusia untuk Sekolah Dasar - Bahtiar, Hariman; Dina Sopiana; Muh. Adrian Juniarta Hidayat; Martua Hamonangan Nasution (Jurnal PRINTER: Jurnal Pengembangan Rekayasa Informatika dan Komputer, 2025)
Education is an essential component in the development of every individual, particularly for elementary school students. In the context of modern education, learning objectives play a crucial role. Observations at SDN 1 Korleko revealed that conventional teaching methods and the use of simple learning media are still dominant, while interactive learning media have not been optimally utilized. Approximately 57.89% of 19 students interviewed reported difficulties in learning due to the lack of engaging media and the occasional complexity of teachers’ explanations. Therefore, this study aims to design and develop interactive learning media with the assistance of Artificial Intelligence (AI). The development of this media is expected to overcome limitations of time and resources in conventional learning, while also fostering students’ interest and motivation. The findings show that the interactive learning media on human organs achieved a success rate of 88%, indicating that it was well received and effective in supporting learning objectives at SDN 1 Korleko. Thus, the use of interactive learning media can serve as an effective alternative to improve the quality of education in elementary schools and is expected to make a significant contribution to the development of innovative learning media that can be adopted by other educational institutions.